(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Income inequality refers to disparities in prosperity, living standards, and the income received or generated by individuals or households within a society. These disparities often result in regional imbalances due to uneven access to production factors and available resources. This study aims to examine the influence of regional own-source revenue (PAD), government expenditure, and investment on income inequality in West Sulawesi. Using a descriptive quantitative approach, the study applies multiple linear regression analysis to time-series data from 2017 to 2022, measured on a weekly basis. The findings reveal that PAD is strongly and significantly correlated with government expenditure and income inequality. However, PAD and government expenditure show no significant correlation with investment, nor do government expenditure and investment significantly correlate with income inequality. Causally, the third sub-structure model indicates that PAD, government expenditure, and investment all have a positive but statistically insignificant influence on income inequality. While PAD reflects a region’s financial independence, its effect on inequality is limited due to uneven distribution. High PAD levels tend to be concentrated in more developed regions with large economic sectors, thus offering little benefit to underdeveloped areas.